Psychiatric Squele of Sodium Valproate Versus Carbamazipine In Patients with Primary Generalized Epilepsy - Hasan, Zeki Noah; Al Yasiri, Abdul- Rasul; Hassan, Hassan Aziz (AL-Kindy College Medical Journal, 2008)
Background: psychiatric and behavioral side effectsare common in patients with epilepsy and it mayrepresent an intrinsic feature of the disease itself or aside effect of the antiepileptic use. Our aim in thepresent study is to assess the psychiatric side effects ofSodium Valproate and Carbamazipine .as these drugsare the most commonly used antiepileptic drugs in Iraq.Methods: 80 patients with primary generalizedepilepsy on Carbamazipine and 50 patients on SodiumValproate were enrolled in the present study; all thepatients were assessed for any psychologicaldisturbances using semi-structural interview based onthe tenth edition of the international classification ofthe diseases(ICD 10) adopted by WHO.Results: Thirty percent of patients taking SodiumValproate and (9%) of patients taking Carbamazipinewere found to have depression while (16%) of patientstaking Sodium Valproate and (20 %) of patients takingCarbamazipine were found to have anxiety. There wereno reported psychosis, suicidal attempts, cognitivedeficit and mania in both groups of patients in thepresent study.Conclusion: Carbamazipine is preferred to SodiumValproate when the efficacy of both drugs iscomparable.